Chinese auditors' views about independence and employer values - Fan, Ying; Woodbine, Gordon; Scully, Glennda (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to describe the results of a cross-sectional survey of Chinese auditors that examines their views about independence and client relationship issues associated with the current Code of Professional Conduct. The paper also compares the findings with attitudes about the perceived ethical environment of their workplaces. Design/methodology/approach – During late 2006, 578 useable questionnaires were obtained from members of the Chinese Institute of Public Accountants registered with four regional chapters. The empirical research was exploratory and involved the construction of a scale for measuring attitudes towards independence issues and a modified version of the Corporate Ethical Values scale. Findings – It was found that auditors clearly identify with the importance of codes of practice and indicate that their views are significantly affected by observations about the ethical climates associated with their immediate workplaces. Codes of practice are seen to be relevant the greater the concern about the ethicality of their workplaces, although attitudes were tempered when client relationship matters are considered, suggesting that some degree of cultural tolerance of questionable activities is inevitable, and that tolerance increases with age. Originality/value – The paper is the first to directly access Chinese practitioners in order to measure attitudes towards western-based standards of practice in association with their workplace conditions. It is a sizable survey, providing useful insights into how practitioners are coping with the demands of their profession in China.